Next Generation Antennas Based on Screen‐Printed and Transparent Silver Nanowire Films. Issue 21 (8th August 2019) - Goliya, Yash; Rivadeneyra, Almudena; Salmeron, José F.; Albrecht, Andreas; Mock, Josef; Haider, Michael; Russer, Johannes; Cruz, Bruna; Eschlwech, Philipp; Biebl, Erwin; Becherer, Markus; Bobinger, Marco R.
Abstract: The advent of mobile communication has made antennas omnipresent. Conventional methods of antenna manufacturing cannot address the growing demands for novel applications requiring transparent and flexible antennas. In this paper, transparent silver nanowire films are studied with respect to their high‐frequency properties. Transparent silver nanowire (AgNW)‐based antennas that are screen printed onto flexible polyethylene terephthalate (PET) substrate are reported. Transparent films with a low sheet resistance of 8.5 Ω sq −1 and a high transmittance of 85%, at a wavelength of 550 nm, are characterized as bowtie antennas with a radiation efficiency of 52%. This combination of efficiency and transmittance rivals the ones that are commonly reported for conductive‐oxide based transparent antennas and paves their use for any automobile window, liquid crystal display, or organic‐light‐emitting‐diode display. Abstract : For the first time, screen printing is employed to manufacture silver nanowire based flexible antennas. Different antenna designs are implemented and studied with respect to their radiation efficiency, sheet resistance, and transmittance. The best antennas exhibit a radiation efficiency of 52% at an optical transmittance of 85%. These performance parameters rival the ones of metal oxide based antennas.